Infaq and Shadaqah Muhammadiyah (LAZISMU) Charitable Institutions Contribution to Muhammadiyah University Semarang (UNIMUS) For Students during the C-19 Pandemic - Rohmat Suprapto; Mardiyan Hayati; Dewi Rohmatul Adhimah; Qomariyatul Intani; Shofi Andini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the contribution of UNIMUS amil zakat infaq and shadaqah (LAZISMU) institutions through the provision of scholarships to UNIMUS students during the covid-19 pandemic. This research was conducted at the University of Muhammadiyah Semarang. The research method used in this research is descriptive qualitative. The qualitative descriptive method used in this study serves to describe and analyze the contribution of LAZISMU UNIMUS during the covid-19 pandemic. The sampling technique used purposive sampling technique; the data was taken with certain considerations. The sample used in this study were UNIMUS students who received educational scholarships and living expenses from LAZISMU UNIMUS during the C-19 pandemic. Data collection techniques were obtained by distributing online questionnaires via google forms to respondents and also through documentation. Sources of data used in this study are primary and secondary data sources. To see the validity of the data used triangulation method. Data analysis was carried out with the first stage of cross-checking, second classification, and third verification, and the last step of data analysis. The results of the analysis show that 1) the biggest impact faced by UNIMUS students is the issue of education costs, which is 73%. 2) LAZISMU UNIMUS' contribution during the C-19 pandemic was scholarship assistance in the field of education in the form of undergraduate scholarships and living expenses. 3) LAZISMU UNIMUS made a very large contribution during the C-19 Pandemic, with 82% stating the role of LAZISMU UNIMUS in contributing to tuition and living expenses.